Climate change and International River Boundaries: fixed points in shifting sands. (17th September 2014) - Grainger, Sam; Conway, Declan
Abstract : The impacts of climate change will have far reaching consequences for transboundary water resources, particularly through the effects of changing frequency and intensity of extreme events, such as floods and their impacts on river channel systems. Watercourses have been used as boundaries throughout history for a variety of reasons, and as both a natural resource and political structure, they present a number of unique challenges. Despite academic studies looking broadly at the effects of changes in runoff on river ecosystems and their resources, less attention has been paid to the socio‐political interactions and consequences for river functionality, in particular, as a boundary. We review the historical and legal role of International River Boundaries highlighting the paradox that exists between the stability needed for a boundary and the dynamism of fluvial landscapes in a changing climate. We draw attention to the fact that geopolitical concerns exist at other unstable border situations, such as ice‐covered boundaries and lakes. We examine the knowledge gaps that exist in relation to understanding the physical impacts of climate change on terrestrial earth systems. We present an exploratory analysis of physical and political risk in Southern Africa that highlights two cases of potential risk. The paper ends with a discussion of actions to address the physical and social dimensions of this strategic issue. WIREs Clim Change 2014, 5:835–848. doi: 10.1002/wcc.306 This article is categorized under: Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change